K-pop netizens exploration on K-pop fan's participation in media consumption and production - De Guzman, Marion Beatrice M. (2018)
The research explored on how different factors affect the participation of K-pop fans from Facebook fan groups? in media consumption and production, and how the participation of a fan is correlated with the existing power relations in a fandom. Using Henry Jenkins? Textual Poachers and convergence Culture, the researcher was able to unearth several factors that affect the participation of the 10 K-Pop fans from Facebook K-pop fan groups. Findings showed that consumption of media content is integrated in the lives of K-Pop fans. Factors like time, choice, convenience and selectivity are the different factors that affect the participation of K-pop fans in media production and consumption. Fans lessen the time they spend updating themselves on K-pop because of their time and schedule, and they also filter out the media they consume because of their selectivity. Due to the convenience brought by convergence culture, it is easier for fans to be able to participate because they can now do multiple things at the same time. In conclusion, different factors affect the participation of K-pop fans in media production and consumption, it either lessen their participation or allows them to participate more. The research was also able to unearth that participation does not matter to K-pop fans because being an active fan or an admin of a Facebook group do not guarantee authority over other fans. Sometimes, there are instances wherein K-pop fans look up to the more active fans but it does not mean they are better fans than the others.